GLP-1 promoter mediated insulin expression for the treatment of diabetes. - Ahmad, Zalinah; Omar, Abdul Rahman; Rasouli, Mina (2010)
Insulin gene therapy is one of many envisioned alternative treatments of diabetes. Diabetes gene therapy would be possible if insulin could be produced in a regulated and specifically in a sensitive manner dependent on the blood glucose level.Therefore, the present invention relates to a method for the isolation of GLP-1 expressing cells, to nucleic acids sequence construction or vectors useful for isolating GLP-1 expressing cell and to the GLP-1 expressing cells isolated therewith. Furthermore, the inventions relates to a method of nucleic acids sequence construction or vectors under the control of the GLP-1 promoter expressing insulin in a recombinant GLP-1 expressing cell line. The cells of the present invention are particular useful for the treatment of diabetes and may be used in a gene therapy approach to treat diabetes and other disorders related to the nutrient metabloism.